2016
DOI: 10.1155/2016/4095852
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Studies Evaluating Visual and Anatomical Outcomes in Patients with Treatment Resistant Neovascular Age-Related Macular Degeneration following Switching to Treatment with Aflibercept

Abstract: With the introduction of aflibercept, eyes with neovascular age-related macular degeneration (AMD) not responding well to injections of ranibizumab or bevacizumab can be switched to treatment with aflibercept. We carried out a meta-analysis to analyze all available evidence of visual and anatomical outcomes of eyes with resistant neovascular AMD switched to aflibercept at six months. Data from seven retrospective and prospective studies looking at change in best corrected visual acuity (BCVA) and central retin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
31
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 36 publications
5
31
0
1
Order By: Relevance
“…This meta-analysis validates the effectiveness of aflibercept in improving morphology in patients with AMD refractory to ranibizumab and bevacizumab 67,68. This may be because aflibercept binds VEGF-A, VEGF-B, and PlGF, while other anti-VEGFs only bind with VEGF-A.…”
Section: Discussionsupporting
confidence: 65%
“…This meta-analysis validates the effectiveness of aflibercept in improving morphology in patients with AMD refractory to ranibizumab and bevacizumab 67,68. This may be because aflibercept binds VEGF-A, VEGF-B, and PlGF, while other anti-VEGFs only bind with VEGF-A.…”
Section: Discussionsupporting
confidence: 65%
“…Our results are in accordance with studies investigating both the outcome after switching from ranibizumab and/or bevacizumab to aflibercept [3, 814, 18] and after switching from bevacizumab to ranibizumab [5, 15, 16]. Fassnacht-Riederle et al only found minimal functional improvement when switching to aflibercept after initial treatment with ranibizumab and/or bevacizumab: Visual acuity increased about 1.8 letters in ETDRS visual acuity score but did not reach statistical significance [3].…”
Section: Discussionsupporting
confidence: 92%
“…patients who are refractory to ranibizumab (Seguin‐Greenstein et al. ). Hence, a more inclusive systematic review of up‐to‐date knowledge is needed to study the efficacy of aflibercept.…”
Section: Introductionmentioning
confidence: 99%